Regulations, Problems, and Legal Solutions for Online Loan Agreements in Indonesia - Agustini, Shenti; Karo Karo, Rizky Pratama; Tan, Winsherly; Syarief, Elza; Ahmad, Faradina Binti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
The aim of this research is first to analyze regulations regarding online loans, identify legal problems arising from online loans, and find an appropriate legal solution to resolving legal issues with online loans. The method used is normative juridical. The research results found that Indonesia already has written laws to regulate online loans, namely financial services authority regulations. However, this regulation is insufficient in resolving online lending legal problems. Normative inconsistencies, especially regarding capital sourcing regulations, Lack of technical clarity, such as in the implementation of lenders' general meetings, Heavy regulatory burdens for new market entrants (e.g., high equity requirements), Unregulated areas, including lender protection, AI/technology ethics, and secondary market mechanisms. Recommended Legal Solutions: 1) Clarification via OJK Circular Letters (SEOJK); 2) Issuance of Fintech Ethics & Technology Guidelines; 3) Establishment of Credit Risk Protection Schemes; 4) Progressive Evaluation and Stakeholder Dialogues; 5) Harmonization with Other Regulations and the P2SK Law.